PENGARUH KEBISINGANTERHADAP WAKTU PERDARAHAN, WAKTU KOAGULASI, DAN JUMLAH TROMBOSIT TIKUS PUTIH (Rattus norvegicus Berkenhout, 1769) BETINA GALUR WISTAR - , RISANTI NAINTIWAN, Laksmindra Fitria, S.Si.,M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Exposed organism to disturbances which is gripping (stressor), such as noise can trigger complex physiological response mechanism such as stress, until behavior change of that organism. The response of body to stress involved the coordination of the nervous and hormonal systems, which work both of those systems,will affect the cardiovascular system. This research is aimed to study the effect of noise on bleeding time, coagulation time, and number of platelet infemale white rat (Rattus norvegicus Berkenhout, 1769) Winstar strain.48 rats were divided into 5 groups based on the duration of treatments, were 1